What's in a name? Is the science of learning identical to behavior analysis?. Issue 1 (2nd January 2016) - Pear, Joseph J.
ABSTRACT: It is the contention of this paper that the study of learning should be called the science of learning and variation . It is further contended that this science overlaps with behavior analysis but is not synonymous with behavior analysis. Drawing from the example of genetics, this paper outlines why variation should be included in the study of learning and suggests a process by which a succinct name for this science that does not carry excess baggage might be generated. Following that process, the candidate name leornetics is proposed to encompass the study of learning and variation. Examples of how such a name could be useful are also discussed. It is important to note that raising the issue of naming the study of learning and variation does not imply that current names for other aspects of behavioral science (e.g., behavior analysis, behavioral psychology, and behaviorism) should be abandoned or changed.